2004
DOI: 10.1021/ef0301598
|View full text |Cite
|
Sign up to set email alerts
|

DI Diesel Engine Performance and Emissions from the Oxygen Enrichment of Fuels with Various Aromatic Content

Abstract: An experimental investigation was conducted on a direct injection diesel engine using conventional and oxygenated diesel fuels. The main scope is to examine the effect of fuel oxygen enhancement for fuels with various aromatic content on engine performance characteristics and, mainly, on pollutant emissions. A mixture of diethylene glycol dimethyl ether (diglyme) and diethylene glycol dibutyl ether (butyl-diglyme) of approximately 20% by mass were added to a high-paraffinics and two commercial diesel fuels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 22 publications
(88 reference statements)
2
47
0
1
Order By: Relevance
“…DEE is one of the main additives used as oxygenating agents in gasoline technology. DEE and other ethers are added to gasoline to increase their octane number (as an octane enhancer or effective modifier to improve the gasoline octane number, or as blending agents for gasoline) and decrease carbon monoxide emission, and reduce particulate and NO x emissions (in a safe, efficient, cost-effective way) [32,33]. DEE properties are similar to those of gasoline components.…”
Section: Technological Applicationmentioning
confidence: 99%
“…DEE is one of the main additives used as oxygenating agents in gasoline technology. DEE and other ethers are added to gasoline to increase their octane number (as an octane enhancer or effective modifier to improve the gasoline octane number, or as blending agents for gasoline) and decrease carbon monoxide emission, and reduce particulate and NO x emissions (in a safe, efficient, cost-effective way) [32,33]. DEE properties are similar to those of gasoline components.…”
Section: Technological Applicationmentioning
confidence: 99%
“…It was found that DME would generate fewer exhaust pollutants (NO x , hydrocarbons, and carbon monoxide). Moreover, DME does not produce soot [6,8]. Apart from above merits, the global warming potential for DME has been modeled and the results indicate that DME has a global warming potential of 0.1 for a 500-year time horizon, which is much lower than diesel [9].…”
Section: Introductionmentioning
confidence: 99%
“…DEE is one of the main additives used as oxygenating agents in gasoline technology. DEE and other ethers are added to gasoline to increase their octane number (as octane enhancer or effective modifier to improve the gasoline octane number, blending agents for gasoline) and decrease carbon monoxide emission, and reduce particulate and NOx emissions (in a safe, efficient, cost-effective way) [1,2]. DEE properties are similar to gasoline components.…”
Section: Introductionmentioning
confidence: 99%